A validated miRNA profile predicts response to therapy in esophageal adenocarcinoma. Issue 23 (4th August 2014) - Skinner, Heath D.; Lee, Jeffrey H.; Bhutani, Manoop S.; Weston, Brian; Hofstetter, Wayne; Komaki, Ritsuko; Shiozaki, Hironori; Wadhwa, Roopma; Sudo, Kazuki; Elimova, Elena; Song, Shumei; Ye, Yuanqing; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND In the current study we present a validated miRNA signature to predict pathologic complete response (pCR) to neoadjuvant chemoradiation in esophageal adenocarcinoma. METHODS Three patient cohorts (discovery, n = 10; model, n = 43; and validation, n = 65) with locally advanced esophageal adenocarcinoma were analyzed. In the discovery cohort 754 miRNAs were examined in pretreatment tumor biopsy specimens using a TaqMan array. Of these, the 44 most significantly altered between tumors with pCR and non‐pCR were examined in an additional 43 tumors using a Fluidigm 48.48 array. The 4 miRNAs (mir‐505*, mir‐99b, mir‐451, and mir‐145*) significantly predicting pCR in both cohorts were examined in an additional validation cohort (n = 65) using an Illumina array. These 4 miRNAs were used to generate an miRNA expression profile (MEP) score. RESULTS The 4 miRNAs profiled are highly significantly associated with pCR in the model cohort (Ptrend = .008), the validation cohort (Ptrend = .025), and the combined cohort (Ptrend = 4.6 × 10−4). The receiver‐operator characteristic areas under the curves (AUCs) for the MEP score were 0.78 for the model cohort, 0.71 for the validation cohort, and 0.72 for the combined cohort. When combined with clinical variables, the MEP score AUCs increased to 0.89, 0.77, and 0.81, respectively Estimates from logistic regression based on the MEP were determined and used to generate a probability of pCR plot, which identifies a group of patients with very high (≥80%) and very low (≤10%) probability of pCR. CONCLUSIONS The MEP score provides a validated means of predicting pCR to neoadjuvant chemoradiotherapy in esophageal adenocarcinoma that is robust across several analysis platforms. Cancer 2014;120:3635–3641. © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society.